Feedback Control of Dynamic Systems, Global Edition - Franklin, Gene F.; Powell, J; Emami-Naeini, Abbas F.; Powell, David; Powell, J. David; Emami-Naeini, Abbas (Pearson International Content, 2019)
For courses in electrical & computing engineering. Feedback control fundamentals with context, case studies, and a focus on design Feedback Control of Dynamic Systems, 8th Edition, covers the material that every engineer needs to know about feedback control—including concepts like stability, tracking, and robustness. Each chapter presents the fundamentals along with comprehensive, worked-out examples, all within a real-world context and with historical background provided. The text is devoted to supporting students equally in their need to grasp both traditional and more modern topics of digital control, and the author's focus on design as a theme early on, rather than focusing on analysis first and incorporating design much later. An entire chapter is devoted to comprehensive case studies, and the 8th Edition has been revised with up-to-date information, along with brand-new sections, problems, and examples. The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed.